2011
DOI: 10.1172/jci44883
|View full text |Cite
|
Sign up to set email alerts
|

The liver-specific microRNA miR-122 controls systemic iron homeostasis in mice

Abstract: Systemic iron homeostasis is mainly controlled by the liver through synthesis of the peptide hormone hepcidin (encoded by Hamp), the key regulator of duodenal iron absorption and macrophage iron release. Here we show that the liver-specific microRNA miR-122 is important for regulating Hamp mRNA expression and tissue iron levels. Efficient and specific depletion of miR-122 by injection of a locked-nucleic-acid-modified (LNA-modified) anti-miR into WT mice caused systemic iron deficiency, characterized by reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
167
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 228 publications
(185 citation statements)
references
References 76 publications
4
167
0
2
Order By: Relevance
“…Unlike other iron-regulatory proteins, such as ferritin and transferrin receptor 1, which are regulated by RNA-binding proteins, IRP1 and IRP2, our knowledge on the post-transcriptional regulation of HAMP is very limited. An indirect role for microRNAs has been suggested in the regulation of mouse and human hepcidin genes via the targeting of transcriptional activators (17,18). In agreement, our findings in this study also indicated an indirect role for miR-214 in HAMP regulation by saturated fatty acids.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Unlike other iron-regulatory proteins, such as ferritin and transferrin receptor 1, which are regulated by RNA-binding proteins, IRP1 and IRP2, our knowledge on the post-transcriptional regulation of HAMP is very limited. An indirect role for microRNAs has been suggested in the regulation of mouse and human hepcidin genes via the targeting of transcriptional activators (17,18). In agreement, our findings in this study also indicated an indirect role for miR-214 in HAMP regulation by saturated fatty acids.…”
Section: Discussionsupporting
confidence: 92%
“…The results obtained from different databases commonly identified miR-214. Previous studies have also shown that miR-122 indirectly regulates HAMP gene expression by targeting 3Ј-UTR of other upstream iron-regulatory genes, such as Hfe and Hjv (17). We therefore included these two microRNAs in our investigations and determined the expression levels in PA-or solvent-treated HepG2 cells by qPCR as described under "Experimental Procedures."…”
Section: Hamp 3ј-utr Regulation By Are-bp-mentioning
confidence: 99%
See 1 more Smart Citation
“…40,44,45 Serum/plasma levels of miR-122 correlate with hepatic necro-inflammation, liver damage, cell death and increased aminotransferase levels in acute and chronic liver diseases. 44,[46][47][48][49] Interestingly, hepatic and circulating miR-122 levels do not correlate in NAFLD 14,39,[50][51][52][53][54][55] or viral hepatitis 41,47,49,56 although both have been statistically associated with various measures of disease severity in these studies. Together these studies show that miR-122 may play a role in most liver diseases.…”
Section: Microrna-122mentioning
confidence: 62%
“…[37][38][39] It is highly expressed in hepatocytes due to its liver specific transcriptional regulation by hepatic nuclear transcription factors 34,40 and is elevated in most hepatic diseases including hepatitis C virus (HCV) and hepatitis B virus (HBV) infections as well as alcohol and drug-induced liver injury, HCC and NAFLD. 13,14,[37][38][39][40][41][42][43][44][45] There are four miR-122 binding sites in the HCV genome 42 and miR-122 may promote viral replication by direct interaction with seed-sequencebinding to two target sites, S1 and S2, in the 5 0 -UTR of the HCV genome resulting in HCV-RNA genome stabilization and enhanced viral RNA abundance. 42,43 Dedifferentiation of hepatocytes during hepatocellular carcinogenesis is associated with the loss of miR-122.…”
Section: Microrna-122mentioning
confidence: 99%